KUANTIFIKASI MIKROBA PENAMBAT NITROGEN SIMBIOTIK (RHIZOBIUM SP.) DAN NON-SIMBIOTIK (AZOTOBACTER SP.) SELAMA PROSES BUDIDAYA KEDELAI HITAM (GLYCINE SOJA L.) VARIETAS DETAM-1 PADA SISTEM BUDIDAYA DI LAPANGAN - Devanda Putra, Silvester
Soybean is a plant from the Leguminosae family, widely cultivated and utilized in Indonesia. The black soybean is an intercropping plant because of its ability to associate with nitrogen-fixing bacteria. One of the bacteria associated with soybean plants is Rhizobium sp. These bacteria can fix N by forming nodules (symbiotic bacteria). The purpose of this experiment is to find out the abundance of bacteria during cultivation process. The optimal conditions for growing black soybeans are temperature of 22-27 °C and humidity of 75-90%. The analysis of the abundance of bacteria was carried out by the Total Plate Count (TPC) method on Jensen (symbiotic N-fixing bacteria) and Burk (non-symbiotic N-fixing bacteria) medium. Isolation of soil bacteria into the medium was carried out using the scatter plate method. The concentration of bacteria solution used for soil samples every week for each medium is a solution of 10-3, 10-4, and 10-5. Soybeans are planted according to SOP with a C/N ratio of 8, air temperature 21.94 - 26.26 °C, humidity 62.45 - 81.77%, soil pH 5.42 - 6.66, and rainfall 0 - 21.25 mm/day. At the beginning of the vegetative phase (from week 1 to week 5), the abundance of Azotobacter sp. in the rhizosphere was 43.2 x 105 CFU/mL, 10 x 105 CFU/mL, 41.5 x 105 CFU/mL, 24.5 x 105 CFU/mL, 25.5 x 105 CFU/mL, respectively. The amount of Rhizobium sp. in the soil during this phase was 0.7 x 105 CFU/mL, 45.7 x 105 CFU/mL, 29.2 x 105 CFU/mL, 34.6 x 105 CFU/mL, 8.9 x 105 CFU/mL, respectively. The amount of Rhizobium sp. associated with plants, quantified from the nodules weight, was 0.02gram, 0.10 gram, 0.17 gram, 0.20 gram, 0.20 gram, respectively. The number of Azotobacter sp., soil Rhizobium sp., and root nodules weight at the beginning of the flowering phase (R1) was 56 x 105 CFU/mL, 8.5 x 105 CFU/mL, and 0.2 grams, respectively. The number of Azotobacter sp., soil Rhizobium sp., and root nodules weight in the R4 phase (fully developed pods) was 19 x 105 CFU/mL, 9 x 105 CFU/mL, and 0.895 grams, respectively. The number of Azotobacter sp., soil Rhizobium sp., and root nodules weight in the R5 phase (seed formation) was 18.5 x 105 CFU/mL, 7.8 x 105 CFU/mL, 1.33 grams, respectively. The number of Azotobacter sp., soil Rhizobium sp., and root nodules weight nn the R6 phase (full seeds) was 18 x 105 CFU/mL, was 7.1 x 105 CFU/mL, and 0.9 gram, respectively. The number of Azotobacter sp., soil Rhizobium sp., and root nodules weight in the R7 phase (physiological maturity) was 15 x 105 CFU/mL, 5.6 x 105 CFU/mL, and 0.59 grams, respectively. These results indicated that the fluctuation of Rhizobium sp. abundance due to environment effect such as at week 8 there was an increase in root nodule weight because the soil temperature in that week was optimum for the nodulation processed and also the presence of the soybeans plant growth phases itself was the other factor that effect to abundance microbe. Keywords : Azotobacter sp., soybean, Rhizobium sp., root nodules